2016
DOI: 10.4172/2157-7471.1000327
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Bacillus amyloliquefaciens for Biocontrol of Bacterial Wilt of Tomato Incited by Ralstonia solanacearum

Abstract: Fifty seven rhizobacteria were isolated from rhizospheric soil of wilted tomato plants and among them two strains of rhizobacteria, having better antagonistic and plant growth promoting ability were characterized them as Bacillus amyloliquefaciens DSBA-11 and DSBA-12 based on morphological, biochemical, partial gene sequence analysis of 16S rRNA and fatty acid methyl ester analysis. Antagonistic activity of these strains DSBA-11, DSBA-12 was compared with other Bacillus species such as B. subtilis DTBS-5, B. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 34 publications
2
39
0
2
Order By: Relevance
“…The 1 mL of suspension then added 9 mL of sterile water and incubated at 80 o C for 30 min for Bacillus sp. target (Singh et al, 2016). Five times serial dillution then carried out, the fourth and fifth dilutions were cultured on the NA (nutrient agar) medium with spread plate method.…”
Section: Methodsmentioning
confidence: 99%
“…The 1 mL of suspension then added 9 mL of sterile water and incubated at 80 o C for 30 min for Bacillus sp. target (Singh et al, 2016). Five times serial dillution then carried out, the fourth and fifth dilutions were cultured on the NA (nutrient agar) medium with spread plate method.…”
Section: Methodsmentioning
confidence: 99%
“…Although soil solarization has been applied for the control of numerous soil borne pathogens but its role for the management of bacterial wilt has not been much studied. However, the wilt incidence was slightly reduced by 8 weeks of soil solarization with 25 µm thick transparent polyethylene sheet (Sharma et al, 2004;Sharma et al, 2016).…”
Section: Cultural Practicesmentioning
confidence: 98%
“…Several biological control agents like Acinetobacter sp. (Xue et al, 2009), Burkholderia nodosa, B. sacchari, B. tericola, B. pyrrocinia (Nion and Toyota, 2008), bacteriophages (Yamada et al, 2007), Bacillus thuringiensis (Zhou et al, 2008), Bacillus subtilis (Singh et al, 2012a(Singh et al, , 2016, Bacillus sp. (Ramesh et al, 2009;Xue et al, 2009), Enterobacter sp.…”
Section: Biological Controlmentioning
confidence: 99%
“…In India, certain research work has been reported on the bio-control of bacterial wilt disease. The work published by Singh 22 , et. al.…”
Section: Introductionmentioning
confidence: 99%